The relationship of the foot and ankle structure with overuse injuries in licensed footballers: a prospective cohort study - Sahillioglu, A.; Cerrahoglu, L. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: Foot and ankle are some of the most frequently injured places in football players` bodies. Overuse injuries have an insidious onset and can restrain athletes from sports temporary or even permanently. This study aimed to investigate the relationship between the clinical evaluation of the foot and ankle and findings obtained from foot plantar pressure measurements with the development of overuse injury, during the one-year follow-up. METHODS: One hundred licensed football players were included in the study. Presence of joint hypermobility, foot posture assessment, ankle and first metatarsophalangeal joint range of motion measurements, pedobarographic plantar pressure assessment of foot was carried out. Then, the footballers were followed for 12 months for the development of new foot and ankle overuse injuries, and the clinical and pedobarographic data of the footballers with at least one injury were compared with the group without injury. RESULTS: We found asymmetric pressure distribution between the preferred and non-preferred foot in the group who had an injury in the pedobarographic static foot plantar pressure measurements (P=0.040). A statistically significant limitation was found in the ankle eversion, first metatarsophalangeal joint dorsiflexion and ankle plantar flexion degrees in the injured group compared to the uninjured group (P=0.029, P=0.023, P=0.044, respectively). CONCLUSIONS: These findings suggest that impairments in foot plantar pressure distribution and limitations in ankle and foot joint range of motion may be risk factors for the development of foot and ankle overuse injury.